FTO POLYMORPHISM AND PHYSICAL FITNESS IN OBESE SCHOOLCHILDREN AFTER AN INTERVENTION PROGRAM - Moraes,Greice Graziela (2018)
ABSTRACT Introduction: Recent studies have shown that the association of FTO rs9939609 gene polymorphism with obesity depends on the level of the individual’s physical activity. However, there are some studies that evaluated physical fitness, health, and motor performance in relation to the rs9939609 FTO gene polymorphism. Objective: To evaluate how the rs9939609 FTO gene polymorphism affects the results of physical fitness tests related to health and athletic performance in schoolchildren after 4 months of intervention of physical exercise. Method: The rs9939609 FTO gene polymorphism was genotyped in a total of 36 schoolchildren from southern Brazil, aged 8 to 16 years. Body mass index (BMI), health-related physical fitness (cardiorespiratory fitness, abdominal strength/endurance, and flexibility) and motor performance (upper and lower limb strength, agility, and speed) were evaluated. The intervention included exercise strategies based on Physical Education, healthy eating, and oral and postural care. Results: In the experimental group, after the intervention, significant differences were noted in individuals with the TT genotype. These individuals showed improvements in abdominal strength (p=0.025), lower limb strength (p=0.037) and agility (p=0.021). For individuals with the AA/AT genotype, improvements in flexibility (p=0.026), abdominal strength (p=0.002), upper limb strength (p=0.008) and lower limb strength (p=0.001) were observed. However, these differences were not statistically significant when comparing the TT and AT/AA genotypes. Conclusions: The experimental group showed improvements in abdominal strength, lower limb strength, and speed. Yet, individuals with different genotypes (AA/AT and TT) for polymorphism rs9939609 exhibited similar values for indicators of physical fitness, health, and motor performance. Level of Evidence II; Lesser quality RCT.